CANINE BREEDS PREDISPOSED TO DEVELOP DISKOSPONDYLITIS: A RETROSPECTIVE STUDY OF 181 CASES (2009-2018) - COELHO, C. M. M.; ADEODATO, A. G.; BROCK, G. W.; CORREA, C. G.; FERNANDES, M. E. L.; PEDRO, L. G.; ELEUTÉRIO, E.; SILVA, M. F. A.; PEIXOTO, A. J. R. (Ars Veterinaria, 2020)
A study to determine the prevalence and predisposition of dog breeds to develop diskospondylitis (DS) was carried out on a population of 5,497 animals submitted to computed tomography or digital radiography of the spine between 2009 and 2018. Variables such as breed, gender, age, vertebral segment and total number of vertebrae affected were collected and submitted to the prevalence tests, chi-square and odds ratio. A total of 181 dogs presented DS, a prevalence of 3.4%. Of these, 65% were males with a probability 1.6x greater than females (CI 1.17-2.17). Dogs more than 10 years old have a 1.5x higher probability (CI 1.10-2.05), while those between 2-5 years the probability decreases 51% (CI 0.34-0.77). Large dogs (>30 kg; 45%) showed a 3.8x greater chance to develop DS (CI 2.56-5.33) than small dogs (<15 kg; 28%), although the small dogs showed a 34% lower probability (CI 0.24-0.47). The Labrador Retriever breed was 3.7x more likely to develop DS than all the other breeds studied (CI 2.56-5.33) and the French Bulldog, among the small breeds, was 2.8x more susceptible (CI 1.51-5.06). In conclusion older dogs, large dogs, especially Labrador Retrievers, are more likely to develop DS. The French bulldog should be studied further.